2005
DOI: 10.1038/sj.jhh.1001917
|View full text |Cite
|
Sign up to set email alerts
|

High blood pressure is inversely related with the presence and extent of coronary collaterals

Abstract: Patients with hypertension have an increased case fatality during acute myocardial infarction (MI). Coronary collateral (CC) circulation has been proposed to reduce the risk of death during acute ischaemia. We determined whether and to which degree high blood pressure (BP) affects the presence and extent of CC circulation. A cross-sectional study in 237 patients (84% males), admitted for elective coronary angioplasty between January 1998 and July 2002, was conducted. Collaterals were graded with Rentrop's clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 37 publications
2
27
1
Order By: Relevance
“…Although we only measured remodeling in the hypertensive model (where it was reduced, Figure 5B), impaired recovery after arterial obstruction has been well-documented in animal models of diabetes mellitus, 69 hypertension, 70 obesity, 71 metabolic syndrome, 72 and hyperlipidemia. 73 Similarly, human studies have also reported reduced collateral score/status in patients with diabetes mellitus, 42, 43, 66 hypertension, 43, 74, 75 and obesity/metabolic syndrome/hyperlipidemia. 43, 76 As with the exercise studies discussed above, whether these observations reflect rarefaction of native collaterals, impaired remodeling or other mechanisms is not known.…”
Section: Discussionmentioning
confidence: 90%
“…Although we only measured remodeling in the hypertensive model (where it was reduced, Figure 5B), impaired recovery after arterial obstruction has been well-documented in animal models of diabetes mellitus, 69 hypertension, 70 obesity, 71 metabolic syndrome, 72 and hyperlipidemia. 73 Similarly, human studies have also reported reduced collateral score/status in patients with diabetes mellitus, 42, 43, 66 hypertension, 43, 74, 75 and obesity/metabolic syndrome/hyperlipidemia. 43, 76 As with the exercise studies discussed above, whether these observations reflect rarefaction of native collaterals, impaired remodeling or other mechanisms is not known.…”
Section: Discussionmentioning
confidence: 90%
“…In patients with CAD, Kyriakides et al [25] found that well-developed collaterals are found more frequently in hypertensive patients than in nonhypertensive patients. On the other hand, Koerselman et al [26] reported an inverse relation between collaterals and blood pressure. In both studies, collateral assessment was based on visual inspection of coronary angiograms without vessel occlusion, a method known to represent a crude estimate of collateral flow and one particularly lacking sensitivity for small vessels compared to quantitative occlusive pressure measurements [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are other factors that also contribute to this process, and these include the size and condition of the distal segmental lumen of the vessel, blood viscosity, myocardial contractility, coronary vascular resistance [9], and physical activity of the subject [18]. Medical conditions such as high blood pressure [7] and diabetes mellitus [1,20] have been reported to adversely affect the development of functional coronary collateral circulation. Contrary to the latter finding, Zbinden et al [25] found that there was no difference in the coronary collateral flow between diabetic and non-diabetic patients.…”
Section: Discussionmentioning
confidence: 99%